Writing economies and economies of writing. (March 2022) - Dufty-Jones, Rae; Gibson, Chris; Barnes, Trevor
Our introduction to the Exchanges section unpacks the two terms, writing economies and economies of writing, as well as previewing the subsequent nine papers included within the section. We contend first, that the economy cannot exist until it is first written about – 'writing economies'. Here a variety of dates have been suggested as to its first written representation, from roughly 2500 hundred years ago to a mere hundred years. Second, we argue that the pressures on academics to write – 'economies of writing' – have never been more acute than now and bound up with the neoliberalization of the university.